Relationship between Family Support and Independent Activity Daily Living (ADL) in Elderly Post-Stroke at Neurology Polyclinic, Sufina Aziz General Hospital Medan in 2020 - Fitriani Fadillah; Fithriani (Science Midwifery, 2020)
Stroke in the elderly should get attention, especially the family in the form of providing support to the elderly after stroke. Family support for the elderly after stroke is expected to increase the independence of the elderly in daily living (ADL) activities. The purpose of this study was to determine the relationship between family support and the level of independence in activity daily living (ADL) in the elderly after stroke at the Neurology Polyclinic of Sufina Aziz General Hospital Medan. This study uses descriptive correlation with a cross sectional approach. This study was carried out on March 21, 2022 to April 2, 2022. The sampling technique used was accidental sampling with a total of 30 patients. Then the data is processed starting from editing, coding, tabulating, entry and processing. The results showed that the support given by the family to the elderly after stroke who sought treatment at the Neurology Polyclinic of Sufina Aziz General Hospital Medan was quite good and the level of independence in Activity Daily Living (ADL) in the Post-Stroke Elderly at the Neurology Polyclinic of Sufina Aziz General Hospital Medan was mild dependence. Based on the results of the chi-square test, it can be concluded that the relationship between family support and the level of independence in daily living (ADL) in the elderly after stroke at the Neurology Polyclinic of Sufina Aziz General Hospital Medan with p value = 0.012 a<0.05.